Impact of biochar on water retention of two agricultural soils – A multi-scale analysis - Wang, Daoyuan; Li, Chongyang; Parikh, Sanjai J.; Scow, Kate M. (Geoderma, 2019)
The ability of soil to retain water under drought and other extreme hydrological events is critical to the sustainability of food production systems and preserving soil ecosystem services. We investigated the impact of biochar on water retention properties in California agricultural soils in a series of column, lab incubation, and field studies. Results from studies based on similar variables (soil, biochar) were used to demonstrate the impact of biochar on soil-water relations at different scales. The influences of biochar type (softwood, 600–700 °C, low surface area; walnut shell, 900 °C, high surface area), application rate (0, 0.5, 1% wt.), and particle diameter (0–0.25, 0.25–0.5, 0.5–1, 1–2 mm) were investigated. Only the higher surface area biochar increased the field capacity of a sandy soil. Neither biochar, altered the field capacity of the higher clay content soil. The walnut shell biochar with 1–2 mm particle diameter was more effective at increasing field capacity in sandy soils compare to smaller biochar size fractions. Neither biochar affected the wilting point in either soil. Neutron imaging was used to explore potential mechanisms involved in water retention by observing the spatial and temporal distribution of water in and surrounding biochar particles (~ 2 mm diameter). After wetting, water retained in the internal pores of biochar was continuously released to surrounding space (~ 2.2 mm sphere) during a 7-day air drying at room temperature, suggesting that soil water retention is improved via the biochar's intraparticle structure. In the field trial, (6 yr., corn-tomato rotation), neither walnut shell biochar amendment (10 t/ ha, equivalent to 0.5% wt. in lab scale experiments) nor agricultural management practices (organic, conventional) altered the water retention capacity of a silty clay loam soil. These data suggest that biochars with a high pore volume can temporarily increase the field capacity and plant available water in a coarse-textured soil, until biochar internal pores are filled by clay and soil organic matter. Our results suggest that biochar can have a limited impact on soil water retention when biochar pore volume is low, or soil texture is fine. High dosage (≥10 t/ha) of high pore volume biochar with bulky particle size (≥1 mm) can improve water retention of coarse-textured soil with limited capacity of water storage and may improve soil's resilience during hydrological extremes. •High porosity biochar particles improved water retention of coarse-textured soils.•Water release from biochar particle to sand was observed using neutron imaging.•Biochar didn't impact soil water retention in a 6-year field trial (silty clay loam).